Self-reported health in the vicinity of five wind power production areas in Finland - Anu W. Turunen (Environment International, 2021)
In many countries, some people living in the vicinity of wind power production areas report having symptoms that they intuitively associate with wind turbines. Recently public discussions have focused especially on wind turbine infrasound. However, scientific evidence supporting an association is lacking. The aim of this study was to assess the association between exposure to wind turbines and the prevalence of self-reported symptoms, diseases and medications.A cross-sectional questionnaire study (n = 2,828) was conducted in the vicinity of five wind power production areas in Finland in 2015–2016. Each area had 3–16 turbines with a nominal power of 2.4–3.3 MW. The response rate was 50% (n = 1,411). Continuous and categorised (≤ 2.5, > 2.5–5, > 5–10 km) distance between the respondents’ home and the closest wind turbine was used to represent exposure to wind turbines. Wind turbine sound pressure level outdoors could be reliably modelled only for the closest distance zone where the yearly average was 34 dB and maximum 43 dB.The data on symptoms (headache, nausea, dizziness, tinnitus, ear fullness, arrhythmia, fatigue, difficulties in falling asleep, waking up too early, anxiety, stress), diseases (hypertension, heart insufficiency, diabetes), and medications (analgesics for headache, joint/muscle pain and other pain, and medication for sleep disturbance, anxiety and depression, and hypertension) was obtained from the questionnaire. Logistic regression analyses were adjusted for age, sex, marital status, education, work situation, smoking, alcohol consumption, physical activity, body mass index, and hearing problems.Annoyance and sleep disturbance due to wind turbine noise were inversely associated with the distance to the closest wind turbine. The prevalence of symptoms, diseases and medications was essentially the same in all distance categories. In multivariate regression modelling, the odds ratio estimates were generally close to unity and statistically non-significant. Beyond annoyance and sleep disturbance, there were no consistent associations between exposure to wind turbines and self-reported health problems. The results do not support the hypothesis that broadband sound or infrasound from wind turbines could cause the proposed health problems.